Combination of Brønsted and Lewis Polymeric Catalysts for Efficient Conversion of Cellulose into 5‐Hydroxymethylfurfural (HMF) in Ionic Liquids. Issue 5 (30th November 2015) - Shen, Yating; Zhang, Yunlei; Chen, Yao; Yan, Yongsheng; Pan, Jianming; Liu, Meng; Shi, Weidong
Abstract: Stable oil‐in‐water high internal phase emulsions (HIPEs) with an internal phase volume fraction of 85 % were stabilized using Tween 85. The prepared poly(HIPEs) were first investigated as adsorbents to treat water polluted with Cr III, and then the catalysts with Lewis acidic sites was synthesized. The catalysts with Brønsted acidic sites were obtained by ion‐exchanging. The as‐prepared HIPEs–Cr III (PEs–Cr III ) and HIPEs–SO3 H (PEs–SO3 H) possess open‐cell structure, interconnecting pores, and strong acidity, they are utilized as highly efficient catalysts for the conversion of biomass to 5‐hydroxymethylfurfural (HMF). These results showed maximum production yields for cellulose, glucose, and fructose of 37.0 %, 58.0 %, and 80.8 %, respectively. PEs–Cr III and PEs–SO3 H can be very easily recycled at least four times without significant loss of activity. Herein, a new method is presented to transform cellulose by using two catalysts in a one‐pot process for meeting the varying demands involved at different reaction stages. Abstract : Cellulose—Break it down : High internal phase emulsions (HIPEs) are used to prepare poly(HIPEs) with the addition of chromium as catalysts with Lewis acidic sites. Additional catalysts with Brønsted acidic sites are obtained by ion‐exchanging. Then, the two catalysts are applied to the biomass‐to‐HMF conversion by breaking down cellulose. The reactions show good production yields with high catalyst recyclability.